Choice of Human-Computer Interaction Mode in Stroke Rehabilitation - Mousavi Hondori, Hossein; Khademi, Maryam; Dodakian, Lucy; McKenzie, Alison; Lopes, Cristina V; Cramer, Steven C (Neurorehabilitation and neural repair, 2016)
Advances in technology are providing new forms of human-computer interaction. The current study examined one form of human-computer interaction, augmented reality (AR), whereby subjects train in the real-world workspace with virtual objects projected by the computer. Motor performances were compared with those obtained while subjects used a traditional human-computer interaction, that is, a personal computer (PC) with a mouse. Patients used goal-directed arm movements to play AR and PC versions of the Fruit Ninja video game. The 2 versions required the same arm movements to control the game but had different cognitive demands. With AR, the game was projected onto the desktop, where subjects viewed the game plus their arm movements simultaneously, in the same visual coordinate space. In the PC version, subjects used the same arm movements but viewed the game by looking up at a computer monitor. Among 18 patients with chronic hemiparesis after stroke, the AR game was associated with 21% higher game scores (P = .0001), 19% faster reaching times (P = .0001), and 15% less movement variability (P = .0068), as compared to the PC game. Correlations between game score and arm motor status were stronger with the AR version. Motor performances during the AR game were superior to those during the PC game. This result is due in part to the greater cognitive demands imposed by the PC game, a feature problematic for some patients but clinically useful for others. Mode of human-computer interface influences rehabilitation therapy demands and can be individualized for patients.